Facile preparation of high-performance plywood adhesive from gelatinized corn starch crosslinked with ammonium dihydrogen phosphate - Jia, Yongbo; Luo, Bei; Lee, Seng Hua; Huang, Heming; Wu, Zhigang; Zhou, Bei; Zhou, Xiaojian; Zhang, Jun (Elsevier BV, 2024)
A flame retardant high-performance gelatinized starch (GS)-ammonium dihydrogen phosphate (ADP) wood adhesive, named GS-ADP adhesive was prepared by condensation of GS and ADP under acidic condition. The preparation process of GS-ADP adhesive is very simple by mixing and stirring GS and ADP evenly at room temperature. The results revealed that the GS-ADP adhesive has good storage stability and water resistance, and its wet shear strength is much higher than that of phenolic resin (PF) adhesive. Markedly, the cone calorimeter test results show that G-ADP adhesive has good flame retardancy, and the plywood based on GS-ADP adhesive has good flame retardancy. Meanwhile, it can be seen from dynamic mechanical analysis (DMA) and thermogravimetric analysis (TGA) that GS-ADP has excellent modulus of elasticity (MOE), high glass transition temperature (Tg) and good thermal stability. The findings suggest that GS-ADP could be a viable substitute for PF resin in structural wood fabrication.